Pengaruh Model Pembelajaran Project Based Learning Berbantuan Aplikasi Mathway Terhadap Kemampuan Literasi Numerasi Siswa MTs Darul Mukhlisin - Siti Marwiah; Israq Maharani; Yumira Simamora (Journal on Education, 2024)
Based on the background of the problem in this research, namely the low numeracy literacy skills of class VII students at MTs Darul Mukhlisin Islamic Boarding School due to their lack of ability to learn and participate actively in mathematics lessons, the learning model applied so far seems monotonous which is still centered on teachers and mathematics learning at MTs Darul Mukhlisin Islamic Boarding School, especially in algebra form material, has not implemented the Mathway application. This study aims 1) to determine the effect of the Project Based Learning learning model on the numeracy literacy skills of seventh grade students at MTs Ponpes Darul Mukhlisin, 2) To find out the effectiveness of using Mathway application on numeracy literacy skills of seventh grade students at MTs Ponpes Darul Mukhlisin. This research method uses a combination method (mixed methods), namely a quantitative approach using tests and a qualitative approach using questionnaires to conclude the research results.Based on the results of the t test calculation, it is known that tcount> ttable (10.168> 2.120), then H0 is rejected and H1 is accepted at the significance level α = 5%, so it can be concluded that there is a significant effect of the Project Based Learning learning model assisted by the mathway application on the numeracy literacy skills of VII grade students of MTs Darul Mukhlisin in 2023-2024. Based on students' mathematics skills assisted by Mathway Application using student questionnaire responses, the average value and percentage of each was obtained in the "Very Good" category and the "Good" category. so that the overall score was 1304 and an average of 3.62 with a percentage of 91% in the "Very Good" category. Questionnaires are used to determine student responses or responses to mathematics skills using the Project Based Learning (PjBL) model assisted by the Mathway Application at MTs Darul Mukhlisin.